Rethinking Political Judgement : Arendt and Existentialism - Mrovlje, Maša (Edinburgh University Press, 2018)
How can we reinvigorate the human capacity for political judgement in our uncertain post-foundational world? This book takes up the challenge by calling on 20th-century existentialism, in particular the works of Jean-Paul Sartre, Simone de Beauvoir, Albert Camus and Hannah Arendt